After looking for the asymptotes of the function:


I found the answers y=0, y=-x-1 and y=x+1. This is almost exact: the last one should actually be y=x-1.

To find the result, I substituted x=my+c in the equation, which yielded $m=\pm 1$ and $c=\mp 1$, when c should be only -1. I can't find where I made a mistake. Any idea?


  • $\begingroup$ Is there a reason you used $x=my+c$ rather than $y=mx+c$? It looks possible that there might have been a confusion between $x$ and $y$ , especially since $x=y+1$ is the same as $y=x-1$. $\endgroup$ – Henry Jun 17 '15 at 22:49
  • $\begingroup$ Thanks Henry. It doesn't work with $$ y=mx+x $$, because a $$ m^3*y^3 $$ comes up, which would mean $$ m=0 $$. I would have thought it should produce the same result; I must admit I have not quite fully digested the theory behind it (still looking for a good textbook explaining that). $\endgroup$ – benox Jun 18 '15 at 7:15
  • $\begingroup$ Anyway your second hint was it: I was so convinced the mistake was in the more extended lines I didn't see I used y instead of x at the end of the calculation. $\endgroup$ – benox Jun 18 '15 at 7:27

Let's look for asymptote :

$y=a\cdot x+b$

substitute into original equation:

$x^3\cdot a\cdot (a^2-1)+x^2\cdot (3a^2\cdot b+2\cdot a^2-b)+x\cdot ...+\ const$

so from $a\cdot (a^2-1)=0$, $a=0,1,-1$ use $3a^2\cdot b+2\cdot a^2-b$ to find corresponding b values $b=0,-1,-1$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.